Improved thermal conductivity of ceramic-epoxy composites by constructing vertically aligned nanoflower-like AlN network. Issue 8 (15th April 2022) - Liu, Li; Xiang, Daoping; Wu, Liangqing
Abstract: Ceramic-polymer composites with good thermal conductivity, low dielectric constant and low dielectric loss have significant applicability in microelectronics and wireless communication systems. However, traditional thermal conductivity ceramic-polymer composites – realized simply through the random dispersion of spherical or near-spherical ceramic powder fillers – cannot have both high thermal conductivity and good electrical insulation, which greatly hinders their practical application. In this study, we first used metallic Al powder corroded by ultrasonic cavitation as the aluminium source, and then prepared spherical aluminium nitride (AlN) powders with many nano petals grown on the surface using the melamine-assisted nitriding method; subsequently, the ice-template method was utilized to construct a three-dimensional (3D) AlN framework with vertical columnar holes, and finally, nanoflower-like AlN-epoxy (EP) composites were prepared by vacuum infiltration. The unique nano petal structures on the surface of AlN powder and the welding between AlN nano-petals during vacuum sintering increased the contact area between nanoflower-like AlN powders and lowered their contact thermal resistance. Moreover, the construction of vertical AlN channels was conducive to the formtion of thermally conductive pathways in AlN-epoxy composites. As a result, we obtained ceramic-polymer composites with improved thermal conductivity, among which the composites with 20 vol% nanoflower-like AlN powder had the highest thermal conductivity – 2.26 W/m·K – compared to a pure matrix, which is equivalent to an enhancement of 830%.